Kinetics of Basic Dye Adsorption onto Sphagnum Magellanicum Peat - Elsa G. Contreras; Boris E. Martinez; Luisa A. Sepúlveda; Carolyn L. Palma (Adsorption Science & Technology)
The purpose of this study was to investigate the adsorption of two Basic dyes, i.e. Basic Blue 3 (BB3) and Basic Orange 2 (BO2), onto Sphagnum Magellanicum peat. The equilibrium studies were carried out at 30°C and 45°C, respectively. The equilibrium experimental results were fitted to the Langmuir model to obtain the characteristic parameters. The maximum sorption capacities for each dye were 41 mg/g for BB3 and 92 mg/g for BO2. The magnitude of the a L parameter increased with temperature for both dyes. The batch kinetic studies of Basic dye adsorption onto peat considered the effect of the initial concentrations of the dyes and the peat dosage. The models fitted were first order (Lagergren equation), pseudo-second order (chemisorption mechanism) and intra-particle diffusion. For all the systems studied, the pseudo-second-order model provided the best correlation. The intra-particle diffusion model provided good correlations over the intermediate and final steps of the adsorption process.